Anticancer activity of glycoalkaloids from Solanum plants: A review - Winkiel, Magdalena Joanna; Chowański, Szymon; Słocińska, Małgorzata (Frontiers in Pharmacology, 2022)
Cancer is still one of the main causes of death in the world. For this reason, new compounds that have chemotherapeutic potential are searched for. One of such group of substances is Solanaceae glycoalkaloids (GA). They are natural compounds that show significant antitumor properties, for example, a strong inhibitory effect on cancer cell growth. This activity might result in the induction of tumor cell apoptosis, which can occur via different molecular pathways. The molecular mechanisms of the action of GA are the subject of intensive research, as understanding them could lead to the development of new cancer therapies. The genetic basis for the formation of neoplasms are mutations in protooncogenes, suppressors, apoptosis-controlling, and repair genes, therefore substances with antineoplastic properties may affect the level of their expression or the level of their expression products. Therapeutic compounds can be applied separately or combined with other drugs to increase the efficiency of cancer therapy; they can act on the cell through various mechanisms at different stages of carcinogenesis, inducing the process of apoptosis, blocking cell proliferation and migration, and inhibiting angiogenesis. This review summarizes the newest studies on the anticancer properties of solanine (SN), chaconine (CH), solasonine (SS), solamargine (SM), tomatine (TT) and their extracts from Solanum plants.